Effectiveness of the Mobile Health Care Service for Type 2 Diabetes Patients During COVID-19 Pandemic of Primary Care Cluster in Kang-an Community Prasat District Surin Province - Jamsopon , Kittipop (Journal of Primary Care and Family Medicine (PCFM), 2020)
Background: The pandemic spread of COVID-19 has affected the delivery of health care services among diabetes type-2 patients. This mainly concerns the use of a particular health care facility—the Kang-an primary care cluster located in Prasat district, Surin province, as it prepared for this condition by establishing the mobile health care service. This portable unit services patients directly at home, which provides the continuity of diabetes monitor and care. Then the COVID-19 pandemic occurred. There was no evidence to compare the mobile health care service’s effectiveness to the conventional health care unit in diabetes type-2 patients in treatment outcomes. Methods: We conducted a Quasi-experimental design involving 105 diabetes type-2 patients based in the Kang-an community. Sixty-nine patients were treated at the Kang-an primary care cluster, and thirty-six patients were treated at the mobile health care service. This study uses the paired and unpaired t-test to analyze the differences, using the criteria of fasting plasma glucose and health services satisfaction. Result: There was no difference in the mean of fasting plasma glucose between mobile health care service and conventional groups (P-value=0.197). Regarding health services satisfaction, there was also no difference (P-value=0.098). Conclusion: This study found in the COVID-19 pandemic era, the effectiveness of controlling the fasting plasma glucose and health services satisfaction were not different between the mobile health care service and the conventional health care service.